Synergizing Bureaucratic Reform and the Digital Economy: An Adaptive Policy Analysis of Lamongan Regency - Yuhronur Efendi; Muhammad Chusnul Khitam (Varied Knowledge Journal, 2026)
This study analyzes how adaptive policy connects bureaucratic reform with digital-economic development in Lamongan Regency. It employs a qualitative single-case design and a transparent document-analysis protocol. Documents relevant to the 2021-2025 policy period were retrieved from official planning, regulatory, performance, public-service, and program repositories and selected according to institutional traceability, substantive relevance, temporal fit, and evidentiary content. Data were extracted into a matrix, coded deductively and inductively, triangulated across source types, and checked against contradictory evidence. Limited benchmarking with Banyuwangi and Sumedang was used to identify transferable service-integration practices. The findings show that bureaucratic reform in Lamongan is supported by digital service development, leadership and apparatus capacity building, and results-oriented performance management. In 2024, the regency recorded a bureaucratic reform score of 86.48, an accountability score of 83.18, a public satisfaction index of 88.02, and a public-service compliance score of 93.7. Digital-economic initiatives, including Pasar Online Lamongan and Mall Oleh-Oleh Lamongan, broadened the instruments for market access and enterprise assistance. However, the reviewed documents do not establish a direct causal relationship between these programs and long-term improvements in citizen welfare or business resilience. The study concludes that adaptive local governance requires process and data integration, inclusive multichannel access, cybersecurity, outcome-based evaluation, and institutional continuity beyond individual leadership.